2021
DOI: 10.1021/acs.nanolett.1c00263
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic g-Factor and Spin–Orbit Field in a Germanium Hut Wire Double Quantum Dot

Abstract: Holes in nanowires have drawn significant attention in recent years because of the strong spin-orbit interaction, which plays an important role in constructing Majorana zero modes and manipulating spin-orbit qubits. Here, we experimentally investigate the spin-orbit field in a hole double quantum dot in germanium (Ge) hut wires by measuring the leakage current in the Pauli spin blockade regime. By varying the applied magnetic field and interdot detuning, we demonstrate two different spin mixing mechanisms: spi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 80 publications
1
18
0
Order By: Relevance
“…1f , we use g -factors of 7 and 3.95 for the two dots. With such different g -factors 30 , 31 , 46 , the two-spin states in the (1,1) regime should be spin product states for any magnetic field above 0.1 T. In the following, we focus on two of these resonances, denoted as mode A and mode B in Fig. 1c .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1f , we use g -factors of 7 and 3.95 for the two dots. With such different g -factors 30 , 31 , 46 , the two-spin states in the (1,1) regime should be spin product states for any magnetic field above 0.1 T. In the following, we focus on two of these resonances, denoted as mode A and mode B in Fig. 1c .…”
Section: Resultsmentioning
confidence: 99%
“…The particularly large Rabi frequency in mode A may have been enhanced by the low-energy excited state included in our model (Supplementary Note 2 and 10 ), a fact that has previously been exploited to enhance spin-electric-field coupling 50 , 51 . To obtain a deeper understanding of such strong spin–orbit coupling, anisotropy spectroscopy would be a viable method to reveal the underlying mechanisms 46 , 52 . Even though the Rabi frequency of 540 MHz is limited by unwanted PAT and heating effects at high microwave power, we believe it is still not the upper bound for the Rabi frequency of a GHW hole spin qubit.…”
Section: Discussionmentioning
confidence: 99%
“…Further research by Bychkov and Rashba demonstrated that the Rashba effect also occurs in quasi-2D systems . Over the past few decades, the Rashba effect and Dresselhaus effect have been observed in various systems, such as 2D semiconductors, heterostructures, metal surfaces, 3D bulk materials, and quantum wells. ,, …”
Section: Origin Of Rashba and Dresselhaus Effects In 2d Electron Gasmentioning
confidence: 99%
“…Finally, we point out another application of our results, which is the reverse argumentation of before. By studying the avoided crossing between the ground state singlet and one of the triplet states, one may obtain information about the SOI in the system if the g tensors are known, e.g., from magneto-transport measurements [45,46]. The experimental parameters used when the crossing vanishes, e.g.…”
Section: B Transverse Couplingmentioning
confidence: 99%